2014
DOI: 10.1080/19338244.2014.904266
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Equity Research: Review With Focus on Outdoor Air Pollution Research Methods and Analytic Tools

Abstract: The objective of this study was to review environmental equity research on outdoor air pollution and, specifically, methods and tools used in research, published in English, with the aim of recommending the best methods and analytic tools. English language publications from 2000 to 2012 were identified in Google Scholar, Ovid MEDLINE, and PubMed. Research methodologies and results were reviewed and potential deficiencies and knowledge gaps identified. The publications show that exposure to outdoor air pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 47 publications
0
30
1
Order By: Relevance
“…Some statistical methods used in environmental inequality research may produce biased findings [1, 5]. Although a variety of methods are used to evaluate inequality, many researchers use a regression based approach to quantify the magnitude and direction of the inequality.…”
Section: Resultsmentioning
confidence: 99%
“…Some statistical methods used in environmental inequality research may produce biased findings [1, 5]. Although a variety of methods are used to evaluate inequality, many researchers use a regression based approach to quantify the magnitude and direction of the inequality.…”
Section: Resultsmentioning
confidence: 99%
“…This approach may obviously lead to biased conclusions through “ecological fallacy” that occur when data averaged for a group are used to make conclusions about an individual. 52 The meta-analyses of various pathologies from exposure to low-dose ionizing radiation and estimates of potential mortality risks in exposed populations are commonly limited by heterogeneity between studies. There is high probability that uncontrolled confounding factors in several populations and occupational groups by particular lifestyle factors and higher dose groups (>500 mSv) drive the revealed trends.…”
Section: Evaluation Of Low-dose Radiation Effects: Methodological Issmentioning
confidence: 99%
“…Others find that minorities become over represented as housing and employment constrains their mobility more than other groups (Been and Gupta 1997, Stretesky and Hogan 1998, Mitchell et al 1999, Lercher et al 2005, Richardson et al 2010, Depro et al 2012, Ramirez-Cuesta 2012, Meir 2013, Pais et al 2014. Evidence is also found that poor and minority communities lack capacity for collective action to resist siting of hazardous activities (Hamilton 1993, Hamilton 1995, Hurley 1997, Pastor et al 2001, Saha and Mohai 2005, Laurian and Funderburg 2013 and conversely that middle class communities are better able to expel them (Ramirez-Cuesta 2012).…”
Section: Introductionmentioning
confidence: 99%